Physical Education 2 fitness exercises : college textbook - Punzalan, Michelle D., author; Mondina, Marilou C., author (Intramuros, Manila : Mindshapers, Inc., 2019)
Students will be able to adapt and transfer the movement competency in different contexts like using any training equipment. Also discussed in this chapter are the theory and the description of physical firness and the realted components, through physical activities the s tudent acquired basic knowledge and understanding of body movements, skills and physical fitness test related activity.
Physical education 2 -- Physical Fitness -- Strength/ resistance Training -- Human Movements -- Rhythmic / Gymnastics Exercise program -- Arnis -- Dance.
Bibliography.
In English text.
Keywords: Physical education and training; Gymanstics; Physical fitness